BIOSORPTION OF COPPER (II) BY BROWN SEAWEED SARGASSUM ILICIFOLIUM (TURNER) C. AGARDH - A. B. SABALE,; A. V. WAGHMODE, (The Bioscan, 2010)
The biosorption of copper (II) on Sargassum ilicifolium biomass was investigated. Batch biosorption experiments were conducted to determine the biosorption properties of the biomass and it was observed that the maximum capacity of copper uptake was around 47% at pH 4.5 during one hour with 1000 mg/L of initial concentration and 100mg algal material. Increased biomass 500 mg accelerated the rate of removal of metal to more than 90% at the similar pH value. Fourier transform infrared spectroscopy analysis of algal biomass revealed the presence of amino, carboxyl, hydroxyl and carbonyl group, which are responsible for biosorption of metal ions. SEM analysis revealed cross linkage between the copper ions and the organic functional groups of the biomass.